PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA PADA PT. ADONARA BAKTI BANGSA JAKARTA PUSAT - Sicillia, Mita; Sunarto, Ading; Kencana, Putri Nilam (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The purpose of this study was to determine the effect of compensation and motivation on job satisfaction at PT. Adonara Bakti Bangsa either partially or simultaneously. The method used is the quantitative method. The sampling technique used was saturated sampling with a sample of 115 respondents. Data analysis used validity test data, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are that compensation has a significant effect on job satisfaction with the regression equation Y = 26,290 + 0,517X1, the correlation coefficient value is 0.499, meaning that both variables have a fairly strong relationship with the coefficient of determination of 24.9% and hypothesis testing is obtained t count > t table or ( 2,040 > 1,981). Motivation has a significant effect on job satisfaction with the regression equation Y = 9.517 + 0.814X2, the correlation coefficient value is 0.682 meaning that both variables have a strong relationship with the coefficient of determination of 46.1% and hypothesis testing is obtained t count > t table or ( 7.152 > 1.981 ). Compensation and motivation simultaneously have a significant effect on job satisfaction with the regression equation Y = 6.401 + 0.173X1 + 0.701X2. The value of the correlation coefficient is 0.696, meaning that the independent variable and the dependent variable have a weak relationship with the coefficient of determination of 24.9% while the remaining 75.1% is influenced by other factors. Hypothesis test of calculated F value > F table or (52.668 > 2.69) thus Ho is accepted and Ha is rejected. This means that there is a simultaneous significant influence between Compensation and Motivation on Job Satisfaction at PT. Adonara Bakti Bangsa.